Analyzing Crucial Elements Of Research Data Management - Khamis, Noorli; Ahmadi, Nurul Aqilah; Jano, Zanariah (Medwell Publishing, 2016)
Research data management is essential for an institution. Before planning a research data management,an institution needs to build a research data management policy.Each university needs the policy as a guideline for the implementation of research data management.Therefore, this study aimed to investigate essential elements of research data management policy.A qualitative content analysis was used to gain insights into best practices of data management policy in selected universities.The findings yielded eight standard items of research data management policy utilized by most top universities globally.The findings are useful toward devising a research data management policy for the Malaysian higher institutions to support research data life cycle and to provide improvements in research efficiency.Future studies should focus on implementing the framework and measuring the effectiveness.